2018
DOI: 10.18203/2349-3933.ijam20183872
|View full text |Cite
|
Sign up to set email alerts
|

Electrolyte dysfunction in myocardial infarction patients

Abstract: Background: Myocardial Infarction (MI) is the term given for a state of myocardial necrosis which is secondary to an acute interruption of the coronary blood supply. Severity is dependent on level of occlusion, length of time of occlusion and presence or absence of collateral circulation. Myocardial infarction is now considered part of a spectrum referred to as acute coronary syndrome. It is a spectrum of acute myocardial ischemia that also includes unstable angina (STEMI) and non-ST segment elevation myocardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 8 publications
0
1
0
Order By: Relevance
“…Electrolyte imbalances are common in STEMI subjects (31,32), and heart rhythm is influenced by electrolyte concentration (33). Although hyperkalemic STEMI is rare (34), our study revealed that 28.1% of STEMI subjects with hyperkalemia had RWMA in the LAD territory.…”
Section: Discussionmentioning
confidence: 99%
“…Electrolyte imbalances are common in STEMI subjects (31,32), and heart rhythm is influenced by electrolyte concentration (33). Although hyperkalemic STEMI is rare (34), our study revealed that 28.1% of STEMI subjects with hyperkalemia had RWMA in the LAD territory.…”
Section: Discussionmentioning
confidence: 99%
“…Regulation of the heart's electrical activity depends on a normal level of calcium, potassium, and sodium, whereas optimum contraction of the heart requires calcium, magnesium, and phosphorus 40 . The reduction in serum activities of both Na + and K + following administration of ISO can be attributed to ongoing oxidative damage as a consequence of a free radical attack on the Na + /K + pump causing its impairment 41 . However, pre-treatment with Musa paradisiaca peel extract resulted in the elevation of the electrolytes, Na + and K + , suggesting responsiveness of electrical conductivity of the heart.…”
Section: Discussionmentioning
confidence: 99%